FAST DCT ALGORITHM FOR VIDEO TRANSMISSION - I Wayan Sutaya (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
This paper presents a fast DCT algorithm by using convolution method. Multipliers will be a crucial process in designing a fast DCT algorithm because they take a long time to complete their process. Reducing a number of multipliers is the one way to make a fast DCT algorithm. This paper shows how to reduce multipliers by using two steps: the first step is by grouping transformation matrix to be two groups in which this process uses the folding concept. The second step is by using fast convolution by inspection to minimize multipliers.   Keywords : multiplier, fast DCT, fast convolution, folding.